THE EFFECT OF INHALATION OF CITRUS LEMON AROMATHERAPY ON THE DEGREE OF NAUSEA AND VOMITING IN PREGNANT WOMEN IN TRIMESTER I - Fadhila Destya Fatmawati; Priyatin Sulistyowati; Dwi Astuti (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Background: Pregnancy is a process of fertilization between spermatozoa and ovum, followed by implantation or nidation. During the first trimester of pregnancy, pregnant women usually experience discomfort such as nausea and vomiting. About 50-80% of pregnant women experience nausea and vomiting in early pregnancy, typically between 6-12 weeks of gestation, due to gastrointestinal and psychological distress. One therapy to reduce the discomfort of nausea and vomiting during pregnancy is the use of citrus lemon aromatherapy. Purpose: This study aims to determine the effect of inhaling citrus lemon aromatherapy on the degree of nausea and vomiting (emesis gravidarum) in pregnant women during the first trimester. Methods: This paper uses a type of qualitative research whit a case study design. Results: The results of the nursing implementation stated that after the administration of citrus lemon aromatherapy inhalation, there was a decrease in the PUQE-24 score, namely from the category of moderate nausea and vomiting with a score of 12 to no nausea and vomiting with a score of 3. Conclusion: The effect of inhaling citrus lemon aromatherapy on the degree of nausea and vomiting (emesis gravidarum) in pregnant women during the first trimester is quite effective in helping to reduce nausea and vomiting in pregnant women.